MAKNA GANGGUAN MENTAL PANDANGAN MAHASISWA MUSLIM - Nasichah Nasichah; Layra Wardatulsoleha; Widiasyahna Haqqia; Amelia Assama (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Mental health has become an important issue among students and is often associated with spiritual and psychological conditions. In Muslim communities, mental disorders are frequently understood through both religious and medical perspectives. This study aims to examine Muslim students' perceptions of mental health and the integration of spiritual and clinical approaches. The research used a descriptive quantitative method with questionnaires distributed to 40 Muslim students. The findings show that most respondents believe mental health is closely related to spirituality and support the combination of religious coping and professional treatment in dealing with mental disorders.